HUBUNGAN IBU NIFAS USIA REMAJA TERHADAP KEJADIAN POSTPARTUM BLUES DI WILAYAH KECAMATAN NALUMASARI JEPARA - Rina Saputri; Widya Mariyana; Rinda Intan Sari (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
The postpartum period is a crisis for mothers due to various changes that occur physically, psychologically, and in family structures that require an adaptation or adjustment process. From the records of the Jepara District Health Office in 2021, data obtained from 127 of 392 maternity mothers (32.4%) experienced postpartum blues symptoms between the ages of 17 and 19. This study aimed to determine the relationship of adolescent postpartum mothers to the incidence of postpartum blues in the District of Nalumsari Jepara. This study used an analytical design with a cross-sectional approach. The population in this study were teenage mothers who gave birth in July 2022 at the Nalumsari Health Center Jepara. The sample is 35 respondents utilizing total sampling. The research instrument used the EPDS questionnaire and was analyzed using the Chi-Square statistical test. The results showed that (1) most of the respondents, as many as 20 people (57.1%), were in their late teens (16-19). (2) The incidence of Postpartum Blues in postpartum mothers who did not experience postpartum blues was 14 people (40%), mild postpartum blues were nine people (25.7%), and severe postpartum blues were 12 people (34.3%). (3) the results of the bivariate analysis showed that there was no relationship between postpartum teenage mothers and the incidence of postpartum blues in the District of Nalumsari Jepara (p-value 0.254 > 0.05). The result showed that age was not the main factor in the incidence of postpartum blues; however, it was caused by other factors such as social, psychological, and emotional factors. In addition, a person's maturity level cannot be determined merely by age. It is suggested that mothers who will undergo childbirth should enrich their knowledge about postpartum period psychological adaptation and factors influencing the incidence of postpartum blues by carrying out activities during antenatal care so that there is preparation to undergo the delivery process until postpartum care and baby care appropriately. Keywords: Teenage postpartum mother, Postpartum Blues Occurrence